Photocurable adhesive composition, laminate, and method for producing substrate
By using a combination technology of photocuring adhesive composition and thermally decomposed compounds, the problems existing in the bonding and peeling process of existing thermally cured adhesives and double-sided tapes are solved, and an efficient and environmentally friendly substrate bonding and peeling process is achieved.
Patent Information
- Application Number
- CN202180020290.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-10
- Filing Date
- 2021-03-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-03-09
AI Technical Summary
The existing heat-curing adhesives require high-thermal processes when bonding, resulting in economical degradation and environmental safety problems. The bonding strength of double-sided tape is insufficient, making it difficult to be suitable for parts with low heat resistance and thinning industries.
The photocuring adhesive composition, including monofunctional components, multifunctional components, photopolymerization initiators and thermally decomposed compounds, is used to achieve bonding through photocuring technology, and is easily peeled off by decomposing the thermally decomposed compound in warm water.
The function of easily peeling off the substrate after processing is realized, avoiding the residue of adhesive composition, reducing dependence on high-temperature processes, and improving processing efficiency and environmental safety.
Smart Images

Figure BDA0003839590830000131 
Figure BDA0003839590830000132 
Figure BDA0003839590830000133
Abstract
Description
Technical Field
[0001] The present invention relates to a photocurable adhesive composition, a laminate and a method for producing a substrate. Background Art
[0002] Recently, in the semiconductor or display industry, a process is widely used in which, after completing the preparatory process of manufacturing optical substrates such as optical lenses, glass, silicon wafers, etc. into a stacked structure or bonding them to parts using adhesive materials with adhesive strength such as adhesive sheets, double-sided tapes, and pressure-reducing adhesives, the adhesive materials are peeled off after being manufactured into the required form according to the applicable purpose through processes such as cutting, dicing, and grinding. When using existing thermosetting adhesives, a separate high-heat process is required for bonding, and it is difficult to apply to parts with low heat resistance. In addition, since a high-heat process is required for bonding, it will lead to a problem of reduced economic efficiency, and since organic solvents need to be used, they must be removed by means of complex processes in consideration of environmental safety issues.
[0003] In addition, when using double-sided tape, due to its weak adhesive strength, the high pressure and high heat during cutting may cause separation between the component and the adhesive material or fixation failure, resulting in component breakage or damage, and the dimensional accuracy after the process will decrease. In addition, due to the low thickness accuracy, the uniformity will decrease, making it unsuitable for industrial fields that require thinning.
[0004] In order to solve the above-mentioned problems, a method has been proposed in which a component is fixed by applying a liquid adhesive composition on the component and then bonding it by light curing, and then peeling the cured product from the component. However, due to the residual organic solvent in the process of peeling the fixed component by means of an organic solvent after processing, a part of the dissolved cured product remains on the peeled component, which leads to problems of reduced appearance processing or adhesive strength, and there are also problems of complicated post-processing steps after removing the organic solvent and environmental issues. Summary of the invention
[0005] Technical issues
[0006] An object of the present invention is to provide a photocurable adhesive composition which is used for bonding a substrate to be processed and which can be easily peeled off after processing.
[0007] The above mentioned topics and additional topics will be explained in detail in the subsequent content.
[0008] Technical solutions
[0009] As a means for solving the above-mentioned problems, as one embodiment of the present invention, a photocurable adhesive composition is provided, which includes: a monofunctional component including a monofunctional monomer or oligomer; a polyfunctional component including a polyfunctional monomer or oligomer; a photopolymerization initiator; and a thermally decomposable compound.
[0010] In addition, a laminate is provided, comprising: two or more substrates; and an adhesive layer which is arranged between at least two of the substrates to bond the substrates; wherein the adhesive layer is a cured product of the photocurable adhesive composition.
[0011] In addition, a substrate processing method is provided, comprising: a step of bonding two or more substrates using the photocurable adhesive composition; a step of processing the substrates; and a step of peeling the processed substrates by immersing them in warm water.
[0012] Effects of the Invention
[0013] The photocurable adhesive composition according to one embodiment of the present invention can be easily bonded to a substrate, provide the bonding force required for processing a laminate, and can be easily peeled off after processing without forming residues of the adhesive composition.
[0014] In addition, since the photocurable adhesive composition contains a thermally decomposable compound as a component, the adhesive force can be reduced by decomposing the thermally decomposable compound during the peeling process, thereby making it easy to peel off the substrate. Moreover, since there is no need to immerse in an organic solvent or perform a specific high-temperature process, the substrate can be peeled and recovered without damage.
[0015] The above-mentioned effects and additional effects will be explained in detail in the subsequent content. DETAILED DESCRIPTION
[0016] Before describing the present invention in detail, it should be understood that the terms used in this specification are only used to describe specific embodiments and are not intended to limit the scope of the present invention, which shall only be limited by the appended claims. Unless otherwise mentioned, the technical meanings of all technical terms and scientific terms used in this specification are the same as those commonly understood by persons with ordinary skills.
[0017] Throughout this specification and claims, unless otherwise mentioned, the terms comprise, comprise, and comprising are used only to indicate the presence of the mentioned object, step, or series of objects and steps, and are not intended to exclude any other object, step, or series of objects or steps.
[0018] In addition, unless otherwise clearly stated to the contrary, each embodiment of the present invention may be combined with any other embodiment. Next, the embodiments of the present invention and their effects will be described in detail.
[0019] A photocurable adhesive composition applicable to one embodiment of the present invention may include: a monofunctional component including a monofunctional monomer or oligomer; a polyfunctional component including a polyfunctional monomer or oligomer; a photopolymerization initiator; and a thermally decomposable compound.
[0020] Here, adhesiveness and adhesion have a broad meaning including tackiness and / or adhesion.
[0021] Monofunctional ingredients
[0022] The monofunctional component includes a monofunctional monomer or oligomer, and specifically may include a monofunctional (meth)acrylate monomer or oligomer. By adding the monofunctional component within the preferred range described below, durability, adhesion and close adhesion can be improved, and gas generation during bonding can be avoided, solubility can be improved, and coating properties can be increased, thereby ensuring smooth completion of the operation.
[0023] The monofunctional component is used in an amount of 10 to 60 parts by weight, preferably 15 to 50 parts by weight, relative to the total weight of the composition.
[0024] When the usage amount of the monofunctional component is less than 5 parts by weight, the high viscosity of the solution may lead to problems with material processability such as material coating and degassing. When the usage amount exceeds 50 parts by weight, the low viscosity of the solution may lead to problems with material coating.
[0025] The weight average molecular weight of the monofunctional oligomer may be in the range of 1,000 to 10,000, and specifically in the range of 3,000 to 8,000. If the weight average molecular weight exceeds the range, it may be difficult to control the hardness and strength due to the viscosity adjustment and the change of elastic modulus, thus causing the problem of poor peeling.
[0026] The monofunctional (meth)acrylate monomer or oligomer may specifically be a monomer or oligomer having a monofunctional (meth)acrylate activity, and one or more of them may be used in combination.
[0027] As specific examples, the monofunctional (meth)acrylate may be isobutyl acrylate, tert-butyl acrylate, lauryl acrylate, octadecyl acrylate, methyl methacrylate, alkyl acrylate, cyclohexyl acrylate, isopentyl acrylate, isobornyl acrylate, benzyl methacrylate, benzyl acrylate, 2-hydroxy acrylate, trimethoxybutyl acrylate, ethyl carbitol acrylate, phenoxyethyl acrylate, 4-hydroxybutyl acrylate, ethoxy-diethylene glycol acrylate, methoxy-triethylene glycol acrylate, 2-ethylhexyl-diethylene glycol acrylate, phenoxy polyethylene glycol acrylate. Esters, phenoxydiethylene glycol acrylate, tetrahydrofurfuryl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl acrylate and their methacrylates; acrylates containing halogen compounds such as 3-fluoroethyl acrylate and 4-fluoropropyl acrylate and their methacrylates; acrylates containing siloxane groups such as triethylsiloxyethyl acrylate and their methacrylates; olefins containing aromatics such as styrene and 4-methoxystyrene, etc.
[0028] Multifunctional ingredients
[0029] The multifunctional component may include a multifunctional monomer or oligomer. Specifically, the multifunctional component may include a multifunctional (meth)acrylate monomer or oligomer. The multifunctional component may provide the composition with reliable environmental resistance and excellent adhesion. The multifunctional component is used in an amount of 30 to 70 parts by weight relative to the total weight of the composition, preferably 40 to 60 parts by weight.
[0030] When the amount of the multifunctional component used is less than 30 parts by weight, it may cause problems with the adhesion and bonding properties of the composition or problems with the process due to too low viscosity. When the amount used exceeds 70 parts by weight, it may cause problems with process properties due to too high viscosity.
[0031] The weight average molecular weight of the multifunctional oligomer may be in the range of 1,000 to 10,000, and specifically in the range of 3,000 to 8,000. If the weight average molecular weight exceeds the range, it may be difficult to control the hardness and strength due to the viscosity adjustment and the change of elastic modulus, thus causing the problem of poor peeling.
[0032] Specifically, the polyfunctional (meth)acrylate may be a monomer or oligomer having bifunctional or higher-functional (meth)acrylate activity, and one or more types may be used in combination. For example, examples of the bifunctional (meth)acrylate include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, 2-ethyl-2-butyl-propylene glycol (meth)acrylate, neopentyl glycol-modified trimethylolpropane di(meth)acrylate, stearic acid-modified pentaerythritol diacrylate, polypropylene glycol di(meth)acrylate, 2,2-bis-(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, and 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane.
[0033] Examples of the trifunctional (meth)acrylate include trimethylolpropane tri(meth)acrylate and tris[(meth)acryloyloxyethyl]isocyanurate.
[0034] Examples of tetrafunctional or higher-functional (meth)acrylates include dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0035] Specific examples of the (meth)acrylate oligomer include urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, or mixtures thereof. The photocurable (meth)acrylate oligomer may be used alone or in combination of two or more.
[0036] The urethane (meth)acrylate oligomer is a compound having a urethane bond (-NHCOO-) and at least two (meth)acryloyloxy groups in the molecule. Specifically, it can be a urethanization reaction product of a (meth)acrylate monomer having at least one (meth)acryloyloxy group and at least one hydroxyl group in the molecule and polyisocyanate, or a urethanization reaction product of a urethane compound containing a terminal isocyanate group obtained by the reaction of a polyol with a polyisocyanate and a (meth)acrylate monomer having at least one (meth)acryloyloxy group and at least one hydroxyl group in the molecule.
[0037] Photopolymerization initiator
[0038] The photopolymerization initiator is not particularly limited, and as an example, acetophenone compounds, benzophenone compounds, thioxanthone compounds, benzoin compounds, triazine compounds, etc. can be used.
[0039] The photopolymerization initiator is used in an amount of 0.1 to 10 parts by weight, preferably 0.1 to 5 parts by weight, based on 100 parts by weight of the total of the monofunctional and polyfunctional components.
[0040] When the amount of the photopolymerization initiator used is less than 0.1 parts by weight, the processability may be reduced due to the slow curing speed, and the self-curing may not be achieved. In addition, when the amount used exceeds 10 parts by weight, the transmittance and yellowness index of the material may be reduced.
[0041] Specific examples of the photopolymerization initiator include 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, p-tert-butyltrichloroacetophenone, p-tert-butyldichloroacetophenone, benzophenone, 4-chloroacetophenone, 4,4'-dimethylaminobenzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one and other acetophenone compounds; benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone and other benzophenone compounds; thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2-chlorothioxanthone Thioxanthone compounds such as thioxanthone; benzoin compounds such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzyl dimethyl ketal; and 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2- One or a mixture of two or more selected from the group consisting of triazine compounds such as (p-triyl)-4,6-bis(trichloromethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalen-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphthalen-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-4-trichloromethyl(piperonyl)-6-triazine, and 2-4-trichloromethyl(4'-methoxyphenylvinyl)-6-triazine.
[0042] In addition, as the photopolymerization initiator, a commercially available photopolymerization initiator can be used, for example, Irgacure 2959, 184, 500, 651, 369, 379, 907, 819 and OXE01, Darocure 1173, 1116, 1398, 1174, 1020, TPO, CGI242, Lucirin TPO and TPO-L from BASF, and Esacure one, KS300, KS200, A144, EDB, EHA, 1001M, 1064, KTO46 and 1187 from Lamberti can be used, or a mixture of two or more thereof.
[0043] Thermally decomposable compounds
[0044] As the thermally decomposable compound, a compound that decomposes and generates gas when heated can be used without limitation. The generated gas is not particularly limited, and can be, for example, nitrogen or carbon dioxide. The thermally decomposable compound of the present invention is different from a thermal polymerization initiator. When the photocurable adhesive composition of one embodiment of the present invention is photocured, the reactive compound starts and ends the reaction with the aid of a photoinitiator, and therefore the thermally decomposable compound is a component that does not participate in the photopolymerization reaction.
[0045] The thermally decomposable compound is used in an amount of 0.1 to 5 parts by weight, preferably 0.3 to 3 parts by weight, based on 100 parts by weight of the total of the monofunctional and polyfunctional components.
[0046] When the amount of the thermally decomposable compound used is less than 0.1 parts by weight, the gas generation may be weak and the peeling effect may not be achieved. When it exceeds 5 parts by weight, gas may be generated due to slight heat during the photocuring process and the adhesive force may decrease while curing, thereby causing the cured product to detach from the substrate.
[0047] An example of the thermally decomposable compound may be an organic azo compound, and the organic azo compound may be an azo compound having a structure represented by the following Chemical Formula 1, but is not limited thereto.
[0048] <Chemical Formula 1>
[0049] RN=N-R'
[0050] (In the chemical formula 1, R and R' are each independently a substituted or unsubstituted aryl group or alkyl group having 1 to 30 carbon atoms.)
[0051] Specific examples of the azo compounds include 2,2'-azobis(2-methylpropionitrile), 2,2-azobis(2-methylbutyronitrile), 1,1'-azobis(1-cyclohexanecarbonitrile), 2,2-azobis(isobutyronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 2,2-azobis(2-methylpropionate), 2,2-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2-azobis(N-butyl-2-methylpropionamide) and 2,2'-azobis(2-phenylpropane). One or a mixture of two or more thereof may be used.
[0052] Among them, when using organic azo compounds, because the gas generation amount at the same content is large and has a variety of different thermal decomposition temperatures, it can be easily peeled in warm water, and it is commercially safe and excellent in process efficiency. In addition, in terms of heat resistance, it is preferred to use azo compounds, and it is more preferred to use azo II compounds.
[0053] The thermal decomposition temperature of the thermally decomposable compound may be in the range of 30 to 200° C., specifically 50 to 150° C., and more specifically 60 to 90° C. The thermal decomposition temperature may be a thermal decomposition start temperature.
[0054] In particular, when the peeling process is performed in warm water, an excellent peeling effect can be achieved only when the thermal decomposition temperature of the thermally decomposable compound is within the above range. When the thermal decomposition temperature of the thermally decomposable compound is lower than the above range, thermal decomposition may occur due to the slight heat generated during photocuring, thereby resulting in a problem that the adhesion of the photocurable adhesive composition required for the cutting process cannot be achieved. When the thermal decomposition temperature of the thermally decomposable compound is higher than the above range, the thermal decomposition reactivity may decrease, resulting in insufficient or slow gas generation, further leading to problems of insufficient peeling and reduced processability.
[0055] Specifically, the thermally decomposable compound may be decomposed due to the heat conducted by the heat-conducting medium. For example, a liquid medium such as a solvent or water heated to a specific temperature may be used. In some cases, the decomposition may be performed by heat transfer through air using a heating device. The heat-conducting ring may preferably be warm water within a specific temperature range, but is not limited thereto.
[0056] More specifically, the thermally decomposable compound can be thermally decomposed in warm water within a range of 50 to 90° C. After the substrate is bonded, cured, and cut using the photocurable adhesive composition, the substrate needs to be peeled off, and during the peeling process in warm water, gas is generated due to the decomposition of the thermally decomposable compound, thereby reducing the adhesive force of the adhesive composition, so that the substrate can be easily peeled off into individual pieces.
[0057] Other Ingredients
[0058] The photocurable adhesive composition according to one embodiment of the present invention may further selectively contain the following components.
[0059] As an example, in order to ensure the stability and reliability of the material for a long time under various environments (high temperature, high temperature and high humidity, excessive ultraviolet rays, etc.), 0.05 to 5 parts by weight of a stabilizer may be included.
[0060] When the amount of the stabilizer used is less than 0.05 parts by weight, yellowing may occur in high temperature, high temperature and high humidity environments or the like, or the stabilizer may not function smoothly. When the amount used exceeds 5 parts by weight, the effect as a stabilizer may not be further improved or the physical properties such as light transmittance may be reduced depending on the type of stabilizer used.
[0061] In addition, spherical particles with a size of 5 to 150 μm may be included. Spherical particles can maintain a stable thickness of the solid body and improve the dimensional precision during processing. In addition, when the fixed parts after processing are peeled off in warm water, the particles in the solid body are deformed and the area of the bonding surface is reduced, thereby further improving its peelability.
[0062] Furthermore, in order to improve the adhesive force or adjust the adhesive performance, a tackifier resin may be additionally contained.
[0063] Furthermore, one or more additives selected from the group consisting of epoxy resins, crosslinking agents, ultraviolet stabilizers, antistatic agents, antioxidants, toners, reinforcing agents, fillers, defoaming agents, surfactants, and plasticizers may be included.
[0064] The present invention also provides a photocurable adhesive composition having a complete peeling time of less than 30 minutes when measured by the following measuring method. Specifically, the peeling time may be less than 25 minutes, more specifically less than 10 minutes, and preferably less than 5 minutes.
[0065] <Measurement method>
[0066] After applying a photocurable adhesive composition with a thickness of 50 μm and a diameter of 50 mm on a 75 mm*75 mm, 0.5 T glass plate and bonding the same glass, the accumulated light intensity at a wavelength of 315 to 400 nm using a metal lamp was 1,000 mJ / cm 2 UV curing was performed under the conditions of . The laminate was repeated 10 times by the above method to produce a laminated cured product with a thickness of 500 μm. The obtained test piece was immersed in warm water at 80° C., and the time required for the glass to be completely peeled off from the cured laminate was measured.
[0067] As another embodiment, the present invention provides a cured layer of a photocurable adhesive composition comprising two or more substrates and being arranged between at least two of the substrates to bond the substrates. The photocurable adhesive composition may be the photocurable adhesive composition described above. The number of laminated substrates is not particularly limited and may be within the range of 2 to 20, and the cured layer of the photocurable adhesive composition described above may be arranged between all substrates or between a portion of the substrates.
[0068] The substrate is not particularly limited, and can be glass, metal, plastic, film, sheet, etc., more specifically, glass. In the case of using glass, it can be glass used in display devices, and its thickness is not particularly limited, and can be within the range of 20 μm to 200 μm.
[0069] In the laminate, the bonding strength between the base materials is 1 to 2 based on the following analysis method.
[0070] <Analysis Method>
[0071] After applying a photocurable adhesive composition with a thickness of 50 μm and a diameter of 8 mm on a 25 mm*40 mm, 1.1 T soda-lime glass upper plate and bonding a 25 mm*60 mm, 1.1 T soda-lime glass upper plate, the accumulated light intensity at a wavelength of 315 to 400 nm using a metal lamp was 1,000 mJ / cm 2 The adhesive strength test piece with a diameter of 50 μm and a diameter of 8 mm was produced and stretched and measured at a tensile speed of 300 mm / min.
[0072] When the adhesive strength exceeds 2, the cured product of the photocurable adhesive composition may remain when peeling, while when the adhesive strength is less than 1, the laminate may fall off when processing, making processing difficult.
[0073] As another embodiment of the present invention, there is provided a method for manufacturing a substrate, comprising: a step of forming a stack by disposing a photocurable adhesive composition containing a thermally decomposable compound between two or more substrates; a step of curing the stack by irradiating light to the stack; a step of cutting the stack; and a step of peeling the substrates into individual pieces by immersing the cut stack in warm water.
[0074] In the step of peeling into individual pieces, the temperature of the warm water can be used to decompose the thermally decomposable compound and generate gas, thereby reducing the adhesive force of the adhesive layer and peeling the substrate into individual pieces. Even if the warm water is not stirred, the thermally decomposable compound can be used to easily peel. However, stirring the warm water is not excluded in the present invention.
[0075] The photocurable adhesive composition may be the photocurable adhesive composition as described above, and the description thereof shall apply.
[0076] In the process of forming the laminate, a laminate in which a plurality of substrates are laminated can be formed by applying a photocurable adhesive composition to the first substrate and attaching it to the second substrate, and then semi-curing it, and then attaching the third substrate with the photocurable adhesive composition and semi-curing it. Next, a step of irradiating the laminate manufactured in the above manner with light to fully cure it can be performed. Alternatively, the semi-curing step can be omitted, and curing can be completed at one time after the laminate is formed.
[0077] Next, the laminate obtained in the above manner is cut into a specific size. By cutting the substrate at one time, the processing productivity can be improved, and the problems of contamination such as the attachment of blade residues, the reduction of cutting ability and the precision of cutting dimensions, which occur when the substrate of the film is cut individually, can be solved.
[0078] Next, the cut laminate is immersed in warm water to separate the substrates into individual pieces. The warm water is water at a higher temperature than normal temperature, and the temperature of the warm water may be in the range of 30 to 100° C., specifically, in the range of 50 to 90° C. If the temperature of the warm water is less than the above range, the peeling time may be prolonged and the peeling may be insufficient, while if it exceeds the above range, the process cost may increase.
[0079] Next, the following examples and comparative examples will be referred to for explanation. However, the following examples are only used to illustrate the present invention, and the present invention is not limited thereto. In addition, unless otherwise clearly stated, "parts" and "%" are based on mass.
[0080] Production of photocurable adhesive composition
[0081] Next, as multifunctional (meth)acrylates, "PU 340" and "PU 610" (Multifunctional urethane acrylate oligomer) of Miwon Trading Co., Ltd. were used, and as monofunctional (meth)acrylates, "IBOA" (Isobornyl acrylate) of Sartomer and "PHA-011" (Poly(ethylene glycol)phenyl ether acrylate) of Hannong Chemical were used. As thermally decomposable compounds, "Vazo 64G" (2,2'-azobis(isobutyronitrile), 2,2'-azobis(isobutyronitrile)), "Vazo 88" (2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile)) of DuPont and " P” (tert-butyl peroxybenzoate), and as a photopolymerization initiator, “Igacure 184” (1-Hydroxycyclohexyl phenyl ketone) produced by BASF was used.
[0082] Production Example 1
[0083] A photocurable adhesive composition was prepared by uniformly mixing 60 parts by weight of (A) multifunctional (meth)acrylate, 40 parts by weight of (B) monofunctional (meth)acrylate, 1 part by weight of (C) photopolymerization initiator, and 2 parts by weight of (D) thermally decomposable azo compound at room temperature for more than 6 hours.
[0084] Production Example 2 to Production Example 3
[0085] As shown in the following Table 1, a photocurable adhesive composition was produced in the same manner as in Production Example 1 except that the content of the (D) thermally decomposable compound was changed.
[0086] Production Example 4
[0087] As shown in Table 1 below, a photocurable adhesive composition was produced in the same manner as in Production Example 1 except that the amount of the thermally decomposable compound (D) was changed to 2 parts by weight and the type thereof was changed.
[0088] Production Examples 5 to 7
[0089] As shown in Table 1 below, a photocurable adhesive composition was produced in the same manner as in Production Example 1 except that (A) the polyfunctional (meth)acrylate was changed to 60 parts by weight and its type, and (D) the content of the thermally decomposable compound was changed.
[0090] Preparation Example 8 to Preparation Example 18
[0091] As shown in Tables 2 and 3 below, a photocurable adhesive composition was produced in the same manner as in Production Example 1 except that the content and type of the (D) thermally decomposable compound were changed.
[0092] Test example
[0093] The physical properties of the compositions in the above-mentioned production examples were measured by the following methods. The results are shown in Tables 1 and 2 below.
[0094] Bond strength measurement
[0095] The T-peel test was performed with reference to the American Society for Testing and Materials (ASTM) D 1876. After coating the composition with a thickness of 50 μm and a diameter of 8 mm on a 25 mm*40 mm, 1.1 T soda-lime glass upper plate and bonding a 25 mm*60 mm, 1.1 T soda-lime glass, the cumulative light amount of a metal lamp at a wavelength of 315 to 400 nm was 1,000 mJ / cm 2 The adhesive strength test piece with a diameter of 50 μm and 8 mm was manufactured according to the above method, and the adhesive strength of the manufactured test piece was measured by stretching it at a tensile speed of 300 mm / min using a UTM universal testing machine 5566.
[0096] Warm water peeling time and peeling state measurement
[0097] After coating the composition with a thickness of 50 μm and a diameter of 50 mm on a 75 mm*75 mm, 0.5 T glass plate and bonding the same glass, the accumulated light intensity of a metal lamp at a wavelength of 315 to 400 nm was 1,000 mJ / cm 2UV curing was performed under the conditions of . The laminated body with a thickness of 500 μm was manufactured by repeating the lamination 10 times using the above method. The obtained test piece was immersed in warm water at 80° C., and the time for the glass to be completely peeled off from the cured laminated body and the peeling state were measured according to the following standards.
[0098] Film form: The cured layer of the adhesive composition is peeled off from the glass in the form of a film.
[0099] Adhesion state: The cured layer is not peeled off from the glass and the adhesive remains
[0100] Detached state: The state where part of the glass is detached before the warm water peeling because the adhesive strength decreases as the curing occurs.
[0101] Partial peeling: Due to the large amount of gas generated, only a part of the solidified layer is peeled off and the solidified layer remains in the glass as an adhesive
[0102]
Table 1
[0103]
[0104]
Table 2
[0105]
[0106]
Table 3
[0107]
[0108] Determination of peeling time based on warm water temperature
[0109] The warm water peel test was performed in the same manner as described above, except that the warm water peel test was performed at a temperature of 50 to 90° C. The results are shown in Table 4 below.
[0110]
Table 4
[0111] Composition number Warm water temperature (℃) 50 60 70 80 90 Production Example 3 Stripping time (minutes) 60 30 20` 5 4 Production Example 4 Stripping time (minutes) 90 50 30 15 10
Claims
1. A photocurable adhesive composition comprising: a monofunctional component comprising a monofunctional (meth)acrylate monomer or a monofunctional (meth)acrylate oligomer having a weight average molecular weight in the range of 1,000 to 10,000; a multifunctional component comprising a multifunctional (meth)acrylate oligomer having a weight average molecular weight of 2,400 to 8,000; Photopolymerization initiator; as well as, Thermally decomposable compounds, The thermally decomposable compound is one or more selected from the group consisting of 2,2'-azobis(2-methylpropionitrile), 2,2-azobis(2-methylbutyronitrile), 1,1'-azobis(1-cyclohexanecarbonitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 2,2-azobis(2-methylpropionic acid) dimethyl ester, 2,2-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2-azobis(N-butyl-2-methylpropionamide) and 2,2'-azobis(2-phenylpropane), The monofunctional component is 10 to 60 parts by weight, and the multifunctional component is 30 to 70 parts by weight. The photopolymerization initiator is contained in an amount of 0.1 to 10 parts by weight, and the thermally decomposable compound is contained in an amount of 0.1 to 5 parts by weight, based on 100 parts by weight of the total of the monofunctional component and the polyfunctional component. 2 . The photocurable adhesive composition according to claim 1 , wherein the thermally decomposable compound generates a gas when thermally decomposed. The photocurable adhesive composition according to claim 2 , wherein the gas is nitrogen. 4 . The photocurable adhesive composition according to claim 1 , wherein the thermal decomposition temperature of the thermally decomposable compound is within a range of 30 to 200° C. 5 . The photocurable adhesive composition according to claim 1 , wherein the thermal decomposition temperature of the thermally decomposable compound is in the range of 60 to 90° C. 6 . The photocurable adhesive composition according to claim 1 , wherein the thermally decomposable compound is thermally decomposed in a heat-conductive medium at 50 to 90° C. 7 . The photocurable adhesive composition according to claim 1 , wherein the thermally decomposable compound is thermally decomposed in warm water at 50 to 90° C.
8. The photocurable adhesive composition according to claim 1, wherein the complete peeling time is within 30 minutes when measured by the following measuring method. <Measurement method> After applying a photocurable adhesive composition with a thickness of 50 μm and a diameter of 50 mm on a 75 mm*75 mm, 0.5 T glass plate and bonding the same glass, the accumulated light intensity at a wavelength of 315 to 400 nm using a metal lamp was 1,000 mJ / cm 2 The laminate was cured by UV curing under the conditions of , and the laminate was repeatedly laminated 10 times using the method to produce a laminated cured body with a thickness of 500 μm. The obtained test piece was immersed in warm water at 80° C., and the time required for the glass to be completely peeled off from the cured laminate was measured. 9 . The photocurable adhesive composition according to claim 1 , further comprising particles having a size of 5 to 150 μm.
10. A laminate comprising: More than 2 substrates; as well as, An adhesive layer is disposed between at least two of the substrates to bond the substrates; The adhesive layer is a cured product of the photocurable adhesive composition according to claim 1.
11. The laminate according to claim 10, wherein the bonding strength between the substrates is 1 to 2 based on the following analysis method. <Analysis Method> After applying a photocurable adhesive composition with a thickness of 50 μm and a diameter of 8 mm on a 25 mm*40 mm, 1.1 T soda-lime glass upper plate and bonding a 25 mm*60 mm, 1.1 T soda-lime glass upper plate, the accumulated light intensity at a wavelength of 315 to 400 nm using a metal lamp was 1,000 mJ / cm 2 The adhesive strength test piece having a size of 50 μm and a diameter of 8 mm was prepared by curing the adhesive under the conditions of , and was stretched and measured at a tensile speed of 300 mm / min.
12. A substrate processing method comprising: The step of bonding two or more substrates using the photocurable adhesive composition according to claim 1; a step of processing the substrate; as well as, The stripping step is performed by immersing the processed substrate in warm water.
13. The substrate processing method according to claim 12, wherein the warm water is 50-90°C.
Citation Information
Patent Citations
Adhesive for temporary bonding
JP2010079958A
Composition and method for temporarily fixing members using the same
JP2010100831A